Effect of Development-based Care Programs by Mothers on Growth Indices of Infants with Low Birth Weight - Sara Asadian; Sedigheh Talakub; Alireza Sadeghnia; Mehri Golchin (Mashhad University of Medical Sciences, 2019)
Background: This study aimed to investigate the effect of development-based care programs by mother on low birth weight (LBW) infants after being discharged from hospital. The present research was based on the assumption that there is a difference between intervention and control groups regarding the mean neonatal growth indices on the 15th and 29th days. Methods: This quasi-experimental study was conducted on 60 infants with LBW (1,500-2,500 g) and gestational age of < 37 weeks in Beheshti Hospital, Isfahan, Iran. The study population was selected through convenience sampling method and then randomly divided into two groups of intervention (n=30) and control (n=30). In the intervention group, the mothers received developmental care training, and in the control group, the mothers received routine care. The data collection instrument were questionnaires, tape meter, stadiometer, and baby scale. The height, weight, and head circumference indices were measured and recorded on the 1st, 15th, and 29th days of birth. Results: The repeated measures ANOVA in within-group analysis revealed a significant difference in the mean weight and height indices of the infants between the intervention and control groups on the 1st, 15th, and  29th days of birth (P<0.001). However, there was no significant difference between the two groups in terms of mean head circumference (P<0.05). Also, the Bonferroni post-hoc test showed a significant difference between the intervention and control groups regarding the weight index on the 29th day (P<0.05). Conclusion: The results showed that the intervention could significantly increase the weight index in the infants. Given that some developmental care techniques are low-cost and executable by mothers, and LWB infants are at risk for various disabilities in the future, health managers are advised to utilize this technique to improve the quality of life in these infants.